Fire Performance of Fiber-reinforced Ultra-High-Performance Concrete: A state-of-the-art review - Khan, Mehran; Kai, Mingfeng; Ahmad, Muhammad Riaz; Lao, Jiancong; Dai, Jian-Guo (Journal of Asian Concrete Federation, 2023)
Explosive spalling is a major problem for structures made of ultra-high-performance concrete (UHPC) after being exposed to fire, which hinders their practical applications. To overcome this obstacle, fibers have become an essential constituent of UHPC in past decades. This paper summarizes a state-of-the-art review related to the fire performance of UHPC using single and hybrid fibers. The spalling behavior, spalling mechanism, mechanical properties, and microstructure characteristics of fiber-reinforced UHPC are summarized, and structural performance of fiber-reinforced UHPC members at elevated temperatures is discussed. This review reveals that fire-induced spalling is a significant concern in UHPC, and it can be caused by various mechanisms. The addition of fibers can play a crucial role in preventing spalling, and different mechanisms for different types of fibers have been reported in the literature for UHPC with both single and hybrid fibers. Therefore, fiber hybridization is recommended to enhance the spalling resistance of UHPC. The future directions and challenges for UHPC at both the material and structural levels are discussed.